المحتوى التعليمي في كتاب اللغة العربية للسنة الثالثة ابتدائي من منظار المعلمين ، دراسة وصفية نقدية - مصمودي, دليلة; قدوره, رأفة; فطحيزة علي, نبيللة (University of Eloued جامعة الوادي, 2024)
الملخص: تبلورت هذه الدراسة حول المحتوى التعليمي في كتاب اللغة العربية للسنة الثالثة من التعليم الابتدائي ( الجيل الثاني ) ، وصفا و نقدا بغية انتقاء أهم ما ورد فيه من شوائب ، للتحسين و التطوير من العملية التعليمية /التعلمية ، قد توصلنا لكل هذا بعد التطرق لمدخل سرد أهم المصطلحات المفتاحية لهذا البحث ، و يليه فصلان متلاحمان فيما بينهما بالاعتماد على التحليل تم وصف الكتاب من ناحية الشكل و المضمون ، و من ثم نقده أيضا شكلا و مضمونا ، وصولا الى العمل الميداني الذي جسد أهم الحلول المقترحة من منظار المعلمين وفق خبرتهم ي هذا المجال و عنايتهم الجديرة به. This study was crystallized around the educational content in arabic language book for third year of primary education (second generation) disrobing and criticizing to select the impurities contained in it for improve and develop the educational bearning process . We have achieved all this after dixussing the introduction narrate the most important key terms for this research . It is followed by two chapters that are interconnected based on analyzing the book was derived in terms of form and content than it also criticized in form and content bading to field work which embodied the most important proposed solutions by teacher's views according to their experience in this field and their due care for it
Keywords: المحتوى التعليمي ، الكتاب المدرسي ، العملية التعلمية ، دراسة نقدية ، دراسة وصفية; educationalcontent . textbook educationalprocess. (edited) . critical study . descriptive study